The Implementation of Multiple Intelligence in English Online Learning - Hanie Ika Setyowati (Universitas PGRI Yogyakarta, 2021)
AbstractOnline learning is the alternative solution to carry out the teaching and learning during the pandemic of Covid-19 since the schools in all level are closed. As the number of English online learning practices carried out in Indonesia, there have been numerous barriers faced by the EFL teachers. One of the challenges faced by the EFL teacher is the students’ lack of motivation since the learning process is considered not interesting. Hence, it is paramount to identify the kinds of learning media such as digital platforms and learning applications that accommodate the students’ multiple intelligence.This study implements a literature review by collecting the data from various relevant literature and analyzing qualitatively. The result of this study shows the kinds of learning application as the media to accommodate the students’ multiple intelligence types. Moreover, the result of this study is expected to be a reference for EFL teachers to select and initiate learning media based on the students’ multiple intelligence. Thus the students get motivation in online learning especially in the current situation.Keywords:multiple intelligence, media, motivation